Organization of Psychological, Medicaland Social Support for Children and Adolescents with ASD in Algeria: Methodological Basics and Techniques - Vlasova O.A (Moscow State University of Psychology and Education, 2018)
The article describes the experience of Algerian specialists of organization of support to children with autism spectrum disorders to in Algeria. Algerian children began to receive comprehensive support at the state level two decades ago. The second part of the article describes a case and the organization of treatment for a autistic patient with comorbid mental retardation in a day hospital. The role of the family and parental organizations in the process of psychological, medical and social support of children and adolescents with ASD is considered, as well as the prospects for the development of a comprehensive care system in Algeria in the coming years. Ending. Beginning in no 1 (58), 2018.